Characterization of oligomeric hydroxyalkanoic acids from thermal decomposition of palm kernel oil-based biopolyester - Sin, M.C.; Tan, I.K.P.; Annuar, M.S.M.; Gan, S.N. (2011)
Oligomeric hydroxyalkanoic acids can be prepared by thermal decomposition of the original polyesters at moderate high temperature. In this study, low molecular weight hydroxyl acids were produced by heat treating of saponified palm kernel oil-derived medium-chain-length polyhydroxyalkanoates (mcl-PHA) in the temperature range of 160 degrees-190 degrees C. Thermal stability, glass transition temperature, and degree of crystallinity of mcl-PHA before and after thermal treatments were characterized by Thermogravimetric Analysis and Differential Scanning Calorimetry measurements. Changes in molecular weight and the acidity of decomposition products were investigated by Gel Permeation Chromatography and end group analyses, respectively. An increase in the acidity of oligomeric hydroxyalkanoic acids was observed when the molecular weight of the oligomers decreased. This was primarily due to the formation of thermodynamically stable hydroxyl-carboxylate ions and the protons in aqueous solutions when heat is supplied to the system.